Comment on Jennings, 'Right Relation and Right Recognition in Public Health Ethics: Thinking through the Republic of Health'. (1st July 2016) - Syrett, Keith
Abstract: This paper offers a brief comment on Jennings' preceding paper, focusing on the capacity of a republican approach to public health ethics to facilitate reconceptualization of the right to health in situations of limited resources through a relational reading.